Israel's Associated Regime: Exceptionalism, Human Rights and Alternative Legality. Issue 79 (19th August 2014) - D'Alessandra, Federica
In the context of Israel's declared permanent state of exception, this article focuses on the legal protection awarded to the Palestinian populations under Israeli control. To broaden the discussion over Palestinian people's rights, which generally focuses on the confiscation of land and the right to return, the author consciously focuses on anti-terrorism and security measures, which contribute to the creation of what the International Court of Justice has defined as an 'associated regime' of occupation. The article is divided into three parts. In the first part, the author discusses Israel's domestic obligations towards Palestinians (arguing the case of both Palestinian citizens of Israel, and Palestinian residents) and their de jure and de facto discrimination. The second part discusses the applicability of humanitarian law, specifically the applicability of the Fourth Geneva Convention. This section discusses the applicability of the Convention to both territories and people under Israeli control. The third part discusses the applicability of international human rights law to all territories under Israeli control and delves into the issue of the mutual relationship between the two international legal regimes in the territories under occupation. The article posits that Israel's rationale for the non-applicability of such legislation to the Palestinian territories and populations it controls constitutes a form of 'alternative legality'. The article concludes that Israel's disproportionate application of security practices and anti-terrorism measures to the Palestinian segment of its population violates Palestinian rights protected under Israel's domestic and international legal obligations.